Total Abdominal Wall Transplantation: An Anatomical Study and Classification System. Issue 6 (June 2017) - Light, David; Kundu, Neilendu; Djohan, Risal; Quintini, Cristiano; Gandhi, Namita; Gastman, Brian R.; Drake, Richard; Siemionow, Maria; Zins, James E.
Abstract : Background: Candidates for multivisceral transplantation present with complex defects often beyond traditional reconstructive options. In this study, the authors describe a dissection technique for a total abdominal wall vascularized composite flap. In addition, the authors suggest a classification system for complex abdominal wall defects. Methods: Forty fresh, cadaveric hemiabdomens were dissected, with care taken to preserve the iliofemoral, deep circumflex iliac, superficial circumflex iliac, deep inferior epigastric, and superficial inferior epigastric arteries and corresponding veins. Perfusion patterns of the flaps were then studied using computed tomographic angiography. Results: The deep circumflex iliac, superficial circumflex iliac, deep inferior epigastric, and superficial inferior epigastric arteries were identified along a 5-cm cuff of the iliofemoral artery centered on the inguinal ligament. Perfusion with an intact deep circumflex iliac artery yielded improvement in lateral perfusion based on computed tomographic angiography. Conclusions: The authors propose an algorithm for abdominal wall reconstruction based on defect size and abdominal wall perfusion, and their technique for harvesting a total vascularized composite abdominal wall flap for allotransplantation. Total abdominal wall transplantation should be considered in the subset of patients already receiving visceral organ transplants who also have concomitant abdominal wall defects.